Anaerobic membrane bioreactor (AnMBR) with external ultrafiltration membrane for the treatment of sugar beet vinasse - Bueno, Beatriz Egerland; Muniz Brito, André Luiz; Garcia Rea, Victor. S.; Kurnianto, Rifki Wahyu; Zaiat, Marcelo; van Lier, Jules. B. (Frontiers in Bioengineering and Biotechnology, 2024)
Vinasse, a by-product of ethanol production, is generated at significant rates. While rich in nutrients such as calcium, magnesium, and potassium, its high solids, organic matter, acidity, and sulfate content pose challenges when disposed directly on soil, necessitating treatment. Anaerobic digestion is a viable solution, reducing organic pollution while recovering bioenergy in the form of biogas, aligning with a biorefinery concept. Traditionally, sludge bed reactors and anaerobic contact reactors are utilized for vinasse processing, with sludge granulation being vital for treatment success. However, challenges such as sludge wash-out due to recalcitrant compounds, high solids concentration in the influent, low pH, salinity, and temperature hinder granule formation. Anaerobic membrane bioreactors (AnMBR) offer an alternative, simplifying treatment by integrating intensified pre- and post-treatment units. Due to complete sludge retention, AnMBRs achieve high COD treatment efficiencies, yielding a suspended solids-free, largely disinfected effluent. Therefore, AnMBRs show promise for vinasse treatment, eliminating the need for sludge granulation and producing nutrient-rich effluent with minimal residual organics and suspended solids. In this study, an AnMBR equipped with an inside-out external crossflow ultrafiltration membrane was proposed for the treatment of vinasse. The AnMBR reached a COD removal efficiency of 95 ± 2.6% and produced 0.3 CH4 L. g COD removed -1 working at organic loading rates of 8 g COD. L-1.d-1 and membrane fluxes of 10 LMH. At organic loading rates of 10 g COD. L-1.d-1 and fluxes of 12 and 14 LMH, the COD removal efficiency decreased to 77 ± 11% and 73 ± 7.9%, respectively. The AnMBR technology represents an innovation for wastewater treatment, however, more research using the cross-flow configuration and different types of effluents is needed. Literature studies that address the treatment of sugar beet or sugarcane vinasse using AnMBR are still scarce. This study explored the potentials of AnMBR technology for vinasse treatment and contributes to the dissemination of this technology, opening new possibilities for vinasse processing.